A parametric study of occupational radiation dose in interventional radiology by Monte-Carlo simulations. (October 2020) - Abdelrahman, Mahmoud; Lombardo, Pasquale; Camp, Anna; Duch, Maria A.; Phillips, Christophe; Seret, Alain; Vanhavere, Filip
Highlights: Monte-Carlo simulations used to study occupational dose in interventional radiology. A model for scatter fraction through polynomial and random forest regression. Beam projections has prominent influence on the dose in IR. The scatter fraction is proportional to kVp, added copper filtration and field size. Changing source to detector distance has the least effect on the dose. Abstract: This paper presents the results of a parametric study on the occupational exposure in interventional radiology to explore the influence of various variables on the staff doses. These variables include the angiography beam settings: x-ray peak voltage (kVp), added copper filtration, field diameter, beam projection and source to detector distance. The study was performed using Monte-Carlo simulations with MCNPX for more than 5600 combinations of parameters that account for different clinical situations. Additionally, the analysis of the results was performed using both multiple and random forest regression to build a predictive model and to quantify the importance of each variable when the variables simultaneously change. Primary and secondary projections were found to have the most effect on the scatter fraction that reaches the operator followed by the effect of changing the x-ray beam quality. The effect of changing the source to image intensifier distance had the lowest effect.